Perencanaan Dinding Turap di Tepi Sungai Pada Tanah Lunak - Toyeb, Muhammad; Mubarak, Husni; Ningrum, Puspa; Yazid, Muhammad (Program Studi Teknik Sipil Sekolah Tinggi Teknologi Pekanbaru, 2022)
Stability of soil on the riverbank necessary to considered towards landslide. Especially the location of soil in around it commonly have kinds the soft soil and over deformation. The large lateral earth pressure grant the influence to sheet pile stability. The face problem was embankment placed in riverbank on natural soil. It is potentially occur shear failure on embankment. Aim the study was design sheet pile to own bearing capacity in order to able withhold mainly lateral force. The source data from soil investigation report was SPT and analysis method based on soil properties, load design, lateral earth pressure, moment force. The result based on soil investigation obtained that almost 20 meters depth was soil to overly soft density. Depth of sheet pile was not reached rock soil because it mainly withhold lateral earth pressure. Therefore design of sheet pile planned to using steel sheet pile of Larssen profile 605K with length 12 m and driving depth 7 m along reinforcement to block anchor.